Integrated Analysis Approach of Gear Whine of Commercial Vehicle Drive Axle - Jiang Xiao; Niancheng Guo; Shanheng Yan; Wanyu Sun; Yanyan Zhao; Jian Liu (Jixie chuandong)
Aiming at the rapid diagnosis and optimization of gear excitation whine noise in the forward design of heavy vehicle drive axle， a dynamic response analysis method integrated considering the structural rigidity of drive assembly is introduced. The gear whine noise simulation and experiment are carried out on a sample vehicle equipped with a twin drive axle. The calibration results show that there is a good correlation between calculation and test response. Then， the noise optimization scheme (optimization of transmission error， modification of structure transmission path) is calculated and analyzed， and a significant noise reduction is achieved.